2018
DOI: 10.1080/00131911.2018.1457010
|View full text |Cite
|
Sign up to set email alerts
|

Technology-enhanced learning in coaching: a review of literature

Abstract: The purpose of this review was to address the central theme of technology-enhanced learning (TEL) in coaching. Technology-enhanced learning' (TEL), has become a widely-accepted term for describing the interface between digital technology and teaching. The aim was to consider the evidence of TEL in coach education, and where appropriate the wider educational field. The review sought to contribute to an evidence-base of suggestions that can be promoted and developed inside and outside of coach development struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 59 publications
2
52
0
Order By: Relevance
“…Cushion and Townsend (2018) recently argued that most articles in sport pedagogy simply report the utility of using DigiTech, without examples of context or suggestions for use. We have provided contextual applications of DigiTech and teachers’ suggestions for how/why it can be used through FL.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cushion and Townsend (2018) recently argued that most articles in sport pedagogy simply report the utility of using DigiTech, without examples of context or suggestions for use. We have provided contextual applications of DigiTech and teachers’ suggestions for how/why it can be used through FL.…”
Section: Resultsmentioning
confidence: 99%
“…Given the reported sparsity of knowledge about FL in PE, it is important to gain a greater understanding of its use. This knowledge is particularly important considering the pedagogical uses of DigiTech to support students' learning are not yet clear within either PE, or the broader field of sport pedagogy (Cushion and Townsend, 2018).…”
Section: Flipped Learningmentioning
confidence: 99%
“…The current context of the COVID-19 pandemic allows the use of part of the time at home for professional learning and for activities that would not normally be performed, such as staying with the family 2 , even mentioning the difficulties to handle the technological resources to study 18 . In this sense, aspects related to professional learning by coaches also present emerging issues, especially within the Brazilian context.…”
Section: Handball Coaches and Social Isolationmentioning
confidence: 99%
“…In a review study, Cushion and Townsend 18 pointed out that the difficulties found by coaches on time management are not exclusive to this period and, therefore, greater attention was also suggested for this content during coaches' education. In this sense, if the use of technology content had more attention, this can improve their training planning and professional enhancement, such as helping with time management 18 . Therefore, it is suggested an alignment in the coaches' education courses to ensure that their professional environment needs are being developed with them, as it is known that the learning process has a great impact on coaches' work 29 .…”
Section: Perspectives On Coaches' Professional Learningmentioning
confidence: 99%
“…In this regard, facilitating learning in all its guises (e.g., online, distance, remote, blended/hybrid and traditional) remains a complicated practice that requires the careful planning of content, delivery, assessment and context (Cushion and Townsend, 2018). Here, the authors advocated that, despite the potential merits held by technology enhanced learning environments, the evidence base supporting the integration of technology remains fragmented (Cushion and Townsend, 2018). The subsequent call was for careful consideration of roles, functions and impact in the design of learning environments.…”
Section: Online and Distance Learningmentioning
confidence: 99%